Toward Cardiac Regeneration: Combination of Pluripotent Stem Cell-Based Therapies and Bioengineering Strategies - Mazzola, Marta; Di Pasquale, Elisa (Frontiers in Bioengineering and Biotechnology, 2020)
Cardiovascular diseases represent the major cause of morbidity and mortality worldwide. Multiple studies have been conducted so far in order to develop treatments able to prevent the progression of these pathologies. Despite progress made in the last decade, current therapies are still hampered by poor translation into actual clinical applications. The major drawback of such strategies is represented by the limited regenerative capacity of the cardiac tissue. Indeed, after an ischaemic insult, the formation of fibrotic scar takes place, interfering with mechanical and electrical functions of the heart. Hence, the ability of the heart to recover after ischaemic injury depends on several molecular and cellular pathways, and the imbalance between them results into adverse remodelling, culminating in heart failure. In this complex scenario, a new chapter of regenerative medicine has been opened over the past 20 years with the discovery of induced pluripotent stem cells (iPSCs). These cells share the same characteristic of embryonic stem cells (ESCs), but are generated from patient-specific somatic cells, overcoming the ethical limitations related to ESC use and providing an autologous source of human cells. Similarly to ESCs, iPSCs are able to efficiently differentiate into cardiomyocytes (CMs), and thus hold a real regenerative potential for future clinical applications. However, cells-based therapies are subjected to poor grafting and may cause adverse effects in the failing heart. Thus, over the last years, bioengineering technologies focused their attention on the improvement of both survival and functionality of iPSC-derived CMs. The combination of these two fields of study has burst the development of cell-based three-dimensional (3D) structures and organoids which mimic, more realistically, the in vivo cell behavior. Toward the same path, the possibility to directly induce conversion of fibroblasts into CMs has recently emerged as a promising area for in situ cardiac regeneration. In this review we provide an up-to-date overview of the latest advancements in the application of pluripotent stem cells and tissue-engineering for therapeutically-relevant cardiac regenerative approaches, aiming to highlight outcomes, limitations and future perspectives for their clinical translation.